Oxidation Of Cyclohexane To Cyclohexanol And Cyclohexanone Using H4[α-SiW12O40]/Zr As Catalyst - Aldes Lesbani; Menik Setyowati; Risfidian Mohadi; Dedi Rohendi (Molekul, 2016)
Synthesis and preparation of polyoxometalate H4[α-SiW12O40].nH2O with Zr as support at various weights of Zr 0.01g; 0.05 g; 0.25 g; 0.5 g; 0.75 g; 1 g and 1.25 g to form H4[α- SiW12O40]/Zr was conducted. The compounds from preparation were characterized using FTIR spectroscopy and crystallinity analysis using X-Ray diffraction. Thus H4[α- SiW12O40]/Zr was applied as catalyst for oxidation of cyclohexane to cyclohexanol and cyclohexanone. Oxidation process was studied through reaction time, hydrogen peroxide amount, temperature, and weight of catalyst. FTIR spectrum of H4[α-SiW12O40]/Zr was appeared at wavenumber 771.53-979.84 cm-1 and Zr at 486.06-1481.33 cm-1. Diffraction pattern of H4[α-SiW12O40]/Zr showed that high crystallinity was identified at 2θ 8o-10o and 28.3o. Based on FTIR spectrum and XRD powder pattern, the optimum preparation of H4[α-SiW12O40]/Zr was obtained using 0.5 g of Zr. The catalytic study of cyclohexane using H4[α-SiW12O40]/Zr at 0.5 g of Zr resulted conversion about 99.73%. Catalyst can convert cyclohexane with the highest conversion then used for further deep catalytic investigation. Optimization of oxidation process resulted optimum reaction time at 2 h, 3 mL of hydrogen peroxide amount, 80 oC of temperature, and 0.038 g of catalyst. The GCMS analysis indicated the oxidation of cyclohexane using H4[α-SiW12O40]/Zr at 0.5 g of Zr formed cyclohexanol and cyclohexanone with selectivity 18.77 and 23.57, respectively.